1986
DOI: 10.1111/j.1151-2916.1986.tb07453.x
|View full text |Cite
|
Sign up to set email alerts
|

Compensating Defects in Highly Donor‐Doped BaTiO3

Abstract: Nb-doped BaTi03 has been prepared with various Ba/(Ti +Nb) ratios such that single-phase products will be obtained if the charged donor center is assumed to be compensated in turn by Ba vacancies, Ti vacancies, equal concentrations of the two cation vacancies, oxygen interstitials, or electrons. For air-fired samples, examination by transmission electron microscopy showed that only the composition adjusted for compensation by titanium vacancies was single phase. The other compositions contained a Ti-rich secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
120
1
5

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(148 citation statements)
references
References 9 publications
12
120
1
5
Order By: Relevance
“…Cuando se adiciona La 2 O 3 al BaTiO 3 (12)(13)(14), las posibles ecuaciones de compensación de cargas a considerar se exponen a continuación.…”
Section: Resultados Y Discusiónunclassified
“…Cuando se adiciona La 2 O 3 al BaTiO 3 (12)(13)(14), las posibles ecuaciones de compensación de cargas a considerar se exponen a continuación.…”
Section: Resultados Y Discusiónunclassified
“…En este trabajo no se detectaron vacantes de Ti ionizadas, pero la generación de vacantes de titanio puede ser importante a muy altas concentraciones de aditivo (10,11 . Este es un resultado interesante para el caso de un ion dopante cuyo comportamiento típico es el de un donor en la red de BaTiO 3 .…”
Section: Resultados Y Discusiónunclassified
“…The activity of fluoride in the present study is significant, as indicated from the occur rence of fluorite in association with U -bearing minerals. The mobility of U and the associated high -field strength elements (HFSE, i.e., Zr, Hf, Nb, and Ti) during fluid/rock interaction has been discussed by many authors (e.g., Chan et al, 1986;Rubin et al, 1993).…”
Section: Early High-temperature Alteration Stagementioning
confidence: 99%